PENILAIAN DAYA TARIK OBJEK WISATA RIAM SABADA DESA SEBATIH KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Wigo, Kristianus; Rifanjani, Slamet; Wulandari, Reine Suci (Universitas Tanjungpura, 2020)
Sebatih Village is a village located in Sengah Temila District, Landak Regency, West Kalimantan Province. One of the hamlets in the village of Sebatih is Keranji Birah Hamlet which has interesting natural tourism to visit, such natural objects are rivers and waterfalls and is called Riam Sabada. Riam Sabada cascade is unique with natural environmental conditions. This study aims to determine the natural tourist attraction of Riam Sabada is Sebatih Village, Sengah Temila District. This research was conducted by the descriptive method. Data obtained by direct interviews with respondents about the attractiveness of attractions and fill out a list of questions. The results of the calculation of all the assessment criteria for attraction of Riam Sabada attraction as well as the elements and sub-elements, namely natural beauty 20.5%, the uniqueness of natural resources 18.16%, the amount of potential natural resources 19%, natural resource 21,16 %, sensitivity of natural resources 19.83%, types of nature tourism activities 16.5%, air cleanliness and location no effect 18.83%, vulnerability of encroachment and the fire 18.66%. All elements of attraction assessment by the Riam Sabada tourism are 915.84 and this area has good area attractions (B) to be developed into a tourism object.Keywords: attraction, nature, riam sabada, tourist attraction